Relationship study between transformational leadership style and corporate ethical virtues of an organization : employees' perspective / Khaulah Abu Bakar - Abu Bakar, Khaulah (2016)
Leadership is the pivotal force behind successful and viable organizations, and for performance soaring organizations, ethics practised within their immediate working environment viewed as one of the main contributor to their niche sustainability. Thus, via research study conducted in one of the Malaysian government-linked companies named Permodalan Nasional Berhad (PNB), researcher aimed to answer the question on whether transformational leadership style influences the corporate ethical virtues enhancement within an organization that would eventually lead to strengthen the ethical organizational culture of the organization as well. This study used factors of transformational leadership style as independent variables while corporate ethical virtues positioned as the dependant variable. Distribution of 275 questionnaire resulted in return feedback of 130 questionnaire. Findings of the study showed that, there is high level of corporate ethical virtues that presence within PNB. However, there is no relationship between transformational leadership style and corporate ethical virtues enhancement within PNB.